Cross country mean and volatility spillover effects of food prices: Evidence for Asia and Pacific - Alom, Fardous; Bert, Ward; Baiding, Hu (World Business Institute, 2010)
This paper examines cross country mean and volatility spillover effects of food prices across selected Asian and Pacific countries namely Australia, New Zealand, South Korea, Singapore, Hong Kong, Taiwan, India and Thailand. The principal method of analysis is a set of component GARCH-type models of conditional variance. Mean and volatility spillover effects of food prices are examined across a full (1995-2010) sample and two subsamples (1995-2001 and 2002-2010), using daily food price indices. Main findings of the study are as follows: (1) there is no strong evidence of cross country mean spillover effects of food prices across all samples, (2) the recent subsample of sharp rise of food prices shows more evidence of mean spillover effects than the early subsample, (3) evidence of volatility spillover effects is stronger than mean spillover effects, (4) mixed evidence of volatility spillover effects is reported and (5) no exact direction of spillover effects between exporters and importers is evident; rather mixed evidence of spillover from exporter to importer, exporter to exporter, importer to exporter and geographical proximity can be documented.